1999
DOI: 10.1016/s0006-3495(99)77150-x
|View full text |Cite
|
Sign up to set email alerts
|

Extensibility and Symmetry of Actin Filaments in Contracting Muscles

Abstract: When isometrically contracting muscles are subjected to a quick release followed by a shortening ramp of appropriate speed (V(o)), tension decays from its value at the isometric plateau (P(o)) to <0. 05 P(o) with the same time course as the quick part of the release; thereafter, tension remains at a negligible level for the duration of the shortening ramp. X-ray diffraction data obtained under these conditions provide evidence that 1) at V(o) very few heads form an actomyosin complex, while the number of heads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 16 publications
3
66
1
1
Order By: Relevance
“…The spacing of the 2.7 nm axial reflection, S 2.7 , is 0.25-0.3% larger during isometric contraction than at rest in whole muscles (Huxley et al 1994;Wakabayashi et al 1994;Bordas et al 1999). Similar axial spacing changes were observed for the 5.1 and 5.9 nm layer line reflections from the actin helix.…”
Section: Compliance Of the Myosin And Actinsupporting
confidence: 64%
See 1 more Smart Citation
“…The spacing of the 2.7 nm axial reflection, S 2.7 , is 0.25-0.3% larger during isometric contraction than at rest in whole muscles (Huxley et al 1994;Wakabayashi et al 1994;Bordas et al 1999). Similar axial spacing changes were observed for the 5.1 and 5.9 nm layer line reflections from the actin helix.…”
Section: Compliance Of the Myosin And Actinsupporting
confidence: 64%
“…The estimate of actin filament compliance is less precise than that of myosin filament compliance. Moreover there is evidence for changes in the periodicity of the actin filament related to activation per se (Wakabayashi et al 1994), and for larger changes in actin filament periodicity during the transition between isometric contraction and rapid shortening (Bordas et al 1999). Thus it remains possible that the actin filament, like the myosin filament, can undergo structural transitions associated with changes in axial periodicities that are distinct from an instantaneous compliance.…”
Section: Compliance Of the Myosin And Actinmentioning
confidence: 99%
“…The genetic helix is left handed with 13 monomers over six turns, 39 with a repeat distance b of 36.0 nm when relaxed. 5 Thus the axial spacing is 2.77 nm and the rotation per monomer is -166°. Moreover, sites on the same 'strand' are spaced by 5.54 nm with a rotation of +27.7°.…”
Section: Actin-myosin Interactions In the Filament Latticementioning
confidence: 99%
“…If rotation of actin by myosin does occur in muscle sarcomeres, then it follows that, because the actin filaments are anchored to the Z-disk, cross-bridges should produce twisting of the thin filaments, in addition to rotation, reducing the helical pitch of the actin helix (Nishizaka et al, 1993). Using X-ray diffraction, changes in helical pitch of thin filaments have been observed in active muscle fibers (Bordas et al, 1999;Tsaturyan et al, 2005), although a confounding factor is that the thin filaments also change in length during activation. Bordas et al (1999) observed no difference in helical pitch between fibers at rest versus maximum isometric force, although the thin filaments were longer, suggesting that some twisting did in fact occur.…”
Section: Titin-myosin Interactionsmentioning
confidence: 99%
“…Using X-ray diffraction, changes in helical pitch of thin filaments have been observed in active muscle fibers (Bordas et al, 1999;Tsaturyan et al, 2005), although a confounding factor is that the thin filaments also change in length during activation. Bordas et al (1999) observed no difference in helical pitch between fibers at rest versus maximum isometric force, although the thin filaments were longer, suggesting that some twisting did in fact occur. The helical pitch of actin filaments decreased during unloaded shortening.…”
Section: Titin-myosin Interactionsmentioning
confidence: 99%